Fat Distribution and its Correlation with Insulin Resistance, Androgen Markers, and Proinflammatory Cytokines in Polycystic Ovary Syndrome - de Melo Cavalcante, Rebeca Bandeira; Leão, Lenora Maria Camarate Silveira Martins; Tavares, Ana Beatriz Winter; Lopes, Karynne Grutter; Kraemer-Aguiar, Luiz Guilherme (Hormone and Metabolic Research, 2024)
The high cardiometabolic risk associated with polycystic ovary syndrome (PCOS) may be linked to central fat accumulation. This study compared fat distribution between women with PCOS and controls matched by body mass index. It also sought to determine if insulin resistance (IR), androgens, or inflammatory markers correlate with body composition parameters in PCOS patients. In total, thirty-five women with PCOS and 37 controls, aged 18–40 years, were included. Hormonal/metabolic profiles, inflammatory biomarkers [tumor necrosis factor-alpha (TNF-α and interleukin-6 (IL-6)], anthropometry (waist circumference, waist-to-hip ratio, lipid accumulation product [LAP], visceral adiposity index [VAI]), and body composition assessed through dual-energy X-ray absorptiometry were assessed. The PCOS group exhibited significantly higher androgen levels and markers of IR. However, levels of TNF-α and IL-6 were comparable between the groups. Despite having similar total body fat mass (FM), the PCOS group had excessive central fat, including increased truncal FM and visceral adipose tissue (VAT). In PCOS, androgens were not associated with body fat or its distribution. IL-6 was positively correlated with total and truncal FM, while insulinemia and the homeostatic model assessment for IR were positively associated with VAT, as well as with total and truncal FM. Although anthropometric measurements and indices were positively associated with DXA-derived central FM parameters, our data suggest that LAP is the most effective tool for assessing central fat deposition and metabolic dysfunction in the PCOS patients studied herein. Furthermore, in this population, IR, rather than androgens or proinflammatory cytokines, is more closely associated with abdominal obesity.
Keywords: body composition; trunk fat mass; visceral fat mass; hyperandrogenism; tumor necrosis factor-alpha; interleukin-6